Focussing on the origins of preterm birth: Why understanding aetiology is critical to optimising outcomes. - Jennifer Jardine; Laura Goodfellow; Caroline Ovadia; Anna L David; Catherine Williamson (PLoS Medicine)
Preterm birth is a central determinant of infant morbidity and mortality. Efforts to reduce its incidence must address the disparate underlying causes.